Work engagement in nursing:The role of self-efficacy and optimism - Othman, Noraini; Ghazali, Zahiruddin; Ahmad, Sa'ari (2014)
Within healthcare organizations, nurses as customer-contact employees play an important role in care delivery and health quality.Nursing is an important profession to study because nurses‟ performance has a great impact on the nature and quality of service provided to the patients. This study examined the relationship between self-efficacy and optimism with work engagement.The sample comprised of 205 staff nurses in two public hospitals in Peninsular Malaysia.Statistical results using regression analysis indicated that optimism was positively related to work engagement.On the other hand, self-efficacy was found to have no significant impact on work engagement.Implications of the results, limitations, and future research directions are also presented.